Genome-Wide Association Identifies Risk Pathways for SAPHO Syndrome - Cai, Ruikun; Dong, Yichao; Fang, Mingxia; Fan, Yuxuan; Cheng, Zian; Zhou, Yue; Gao, Jianen; Han, Feifei; Guo, Changlong; Ma, Xu (Frontiers in Cell and Developmental Biology, 2021)
SAPHO syndrome is a chronic immune-mediated condition that reflects the variable combination of synovitis, acne, pustulosis, hyperostosis, and osteitis.  However, little is known about the pathogenesis of SAPHO syndrome. We conducted a genome-wide association study (GWAS) of 49 patients and 121 control subjects to identify common genetic variants associated with SAPHO, the data were analyzed by classical multiple logistic regression. Later, GWAS findings were further validated using whole exome sequencing (WES) in 16 patients and 15 controls to identify potentially functional pathways involved in SAPHO pathogenesis. In general, 40588 SNPs in genomic regions were associated with P < 0.05 after filter process, only 9 SNPs meet the expected cut-off P-value, however, none of them had association with SAPHO syndrome based on published literatures. And then, 15 pathways were found involved in SAPHO pathogenesis, of them, 6 pathways including osteoclast differentiation, bacterial invasion of epithelial cells, et al had strong association with skin, osteoarticular manifestations of SAPHO or inflammatory reaction based published research. This study identified aberrant osteoclast differentiation and other pathways were involved in SAPHO syndrome. This finding may give insight into understanding of the pathogenic genes of SAPHO and provide the basis for SAPHO research and treatment.